ARE THERE CORRELATION BETWEEN STRESS LEVELS AND EATING BEHAVIOR ON THE LAST GRADE STUDENTS OF BACHELOR IN NURSING SCIENCE STUDY PROGRAM - Masroni Masroni; Anita Dwi Ariyani; Rizky Indrawangi (Sekolah Tinggi Pariwisata Mataram, 2023)
Stress is a human's response both physically and emotionally while there may be any alternative within the environment that requires a person to adjust. Many people use food as a coping mechanism to deal with feelings such as stress, boredom, or anxiety. Students who deal with academic stressors are at increased risk of food consumption. This study aims to determine the correlation between stress levels and eating behavior on the last grade students of Bachelor in Nursing Sciences Study Program at STIKES Banyuwangi in preparing their thesis in 2022. This research used cross-sectional design study and total sampling technique. Data were collected by using DASS 42 (Depression Anxiety Stress Scale 42) and DEBQ (Dutch Eating Behavior Questionnaire) and were spread using google form. For the statistical analysis, it was used Spearman Rank test with SPSS version 25 for Windows. The results showed that 35% of students suffered from moderate stress in preparing their thesis and 63% of them experienced moderate eating behavior. The results of analysis obtained significant research results with closeness correlation value of 0.498. It was obtained P-value of 0.000 which means P less than 0.05, thus there was correlation between the two variables and the coefficient value direction was positive. It is very important for the last grade students to improve their ability in managing their stress levels, particularly when they write their thesis, to avoid stress and negative impact of eating behavior.